2016
DOI: 10.18410/jebmh/2016/6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Isometric Hand Grip Exercise Training on Cardiovascular and Echocardiographic Parameters Among Healthy Young Males

Abstract: Low level of physical fitness and sedentary life style is becoming one of the major risk factor of cardiovascular disease morbidity and mortality. Isometric hand grip exercise (IHG exercise) as a form of static resistance exercise has been shown to lower resting blood pressure and results in favorable cardiovascular remodeling. Still, its effect on cardiovascular, especially echocardiographic parameters has not been widely studied. Hence, the study was planned to evaluate the effect of IHG training of 5 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Forty‐seven studies reported the chronic changes in resting blood pressure after isometric handgrip training (Ahmed et al, 2019; Allen et al, 2003; Alomari et al, 2010; Baddeley‐White et al, 2019; Badrov, Bartol, et al, 2013; Badrov, Horton, et al, 2013, 2016; Bank et al, 1998; Baross et al, 2017; Bentley et al, 2018; Cahu Rodrigues et al, 2020; Carlson et al, 2016; Correia et al, 2020; Dempster et al, 2018; Dobrosielski et al, 2009; Farah et al, 2018; Gandhi, 2016; Garg et al, 2014; Goessler et al, 2018; Herrod et al, 2019; Hess et al, 2016; Howden et al, 2002; Lara et al, 2015; McGowan et al, 2006; McGowan, Levy, et al, 2007; McGowan, Visocchi, et al, 2007; Millar et al, 2007, 2008, 2013; Mortimer & McKune, 2011; Ogbutor et al, 2019; Okamoto et al, 2020; Pagonas et al, 2017; Peters et al, 2006, Punia & Kulandaivelan, 2020; Ray & Carrasco, 2000; Saito et al, 2009; Sinoway et al, 1996; Somani et al, 2017, 2018; Somers et al, 1992; Souza et al, 2020; Stiller‐Moldovan et al, 2012; Taylor et al, 2003; Wiley et al, 1992; Yamagata & Sako, 2020; Zhang, 2003) (Table 2). In total, 22 studies included a nonexercise control group, three studies included a sham‐control group, one study provided a lifestyle modification program to both treatment and control groups, and 21 studies only had one or multiple isometric handgrip training groups.…”
Section: Methodsmentioning
confidence: 99%
“…Forty‐seven studies reported the chronic changes in resting blood pressure after isometric handgrip training (Ahmed et al, 2019; Allen et al, 2003; Alomari et al, 2010; Baddeley‐White et al, 2019; Badrov, Bartol, et al, 2013; Badrov, Horton, et al, 2013, 2016; Bank et al, 1998; Baross et al, 2017; Bentley et al, 2018; Cahu Rodrigues et al, 2020; Carlson et al, 2016; Correia et al, 2020; Dempster et al, 2018; Dobrosielski et al, 2009; Farah et al, 2018; Gandhi, 2016; Garg et al, 2014; Goessler et al, 2018; Herrod et al, 2019; Hess et al, 2016; Howden et al, 2002; Lara et al, 2015; McGowan et al, 2006; McGowan, Levy, et al, 2007; McGowan, Visocchi, et al, 2007; Millar et al, 2007, 2008, 2013; Mortimer & McKune, 2011; Ogbutor et al, 2019; Okamoto et al, 2020; Pagonas et al, 2017; Peters et al, 2006, Punia & Kulandaivelan, 2020; Ray & Carrasco, 2000; Saito et al, 2009; Sinoway et al, 1996; Somani et al, 2017, 2018; Somers et al, 1992; Souza et al, 2020; Stiller‐Moldovan et al, 2012; Taylor et al, 2003; Wiley et al, 1992; Yamagata & Sako, 2020; Zhang, 2003) (Table 2). In total, 22 studies included a nonexercise control group, three studies included a sham‐control group, one study provided a lifestyle modification program to both treatment and control groups, and 21 studies only had one or multiple isometric handgrip training groups.…”
Section: Methodsmentioning
confidence: 99%
“…Sandhu et al (2014) found MD of -7.04 mmHg in SBP and -6.56 mmHg in DBP. Gandhi (2016) found MD of -3.24 mmHg in SBP and -4.03 mmHg in DBP. Overall there was a mean reduction of 6.72 mmHg in SBP and 5.28 mmHg in DBP.…”
mentioning
confidence: 91%